Analisis Pengaruh Segmentasi Pasar terhadap Keputusan Pembelian Beras Merah Organik di Supermarket Tiara Dewata - RAGAPADMI, NI NYOMAN AYU CHANDRA; USTRIYANA, I NYOMAN GEDE; WIJAYANTI, PUTU UDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
Analysis of the Influence of Market Segmentation on The Decision to Purchase Organic Red Rice in Tiara Dewata Supermarkets. Market segmentation is basically a way to differentiate the market according to several characters from customers. With the existence of market segmentation in accordance with the diversity of consumer needs in making purchasing decisions, the company will be able to satisfy its consumers. This study aims to This study aims to 1) Analyze the influence of geographical segmentation on the purchasing decision of organic red rice at Tiara Dewata Supermarket 2) Analyze the influence of demographic segmentation on the purchasing decision of organic red rice at Tiara Dewata Supermarket 3) Analyze the influence of psychographic segmentation on the purchasing decision of organic red rice at Tiara Dewata Supermarket 4) Analyze the influence of behavioral segmentation on the purchasing decision of organic red rice at Tiara Dewata Supermarket. The data collection methods in this study are interviews, documentation, and literature studies and use research instruments in the form of questionnaires. The data analysis method used is to use the Structural Equation Modelling-Partial Least Square (SEM-PLS) approach. Hypothesis test results explain that segmentation variables Geographical, Demographic Segmentation, Psychographic Segmentation and Segmentation Behavior partially had a significant effect with t-count values of 2,603, 1,998, 2,790, 3,474 > t-table values of 1,96 and significance levels of respectively, 0,010, 0,046, 0,005, 0,001 < 0.05. The results of this study showed a significant influence on all variable relationships established in the study objectives. Based on the results of the study, the advice that can be given related to this research is that it is hoped that Tiara Dewata Supermarket can continue to expand its sales area in order to reach a wider market and promote consistently through social networks by offering or introducing organic red rice products that are marketed while providing a little overview of the benefits and quality of the product in order to build consumer confidence.